EVALUATION OF SALICYLIC ACID IN THE ex vitro ACCLIMATATION OF MICROPLANTS OF Laelia autumnalis (Lex.) Lind., Epidendrum sp. AND Encyclia sp. - Martha Elena Mora-Herrera; Juan Manuel Olivares-Aguilar; Diana Yatzil Reyes-Araujo; Stephanie Elizabeth Ceballos-Vásquez; Rómulo García-Velasco (Tropical and Subtropical Agroecosystems)
Background: One of the main problems of in vitro propagation of orchids is the loss of specimens during acclimatization. This stage is crucial to promote morphological and physiological changes that allow their adaptation to ex vitro conditions. Salicylic acid (SA), by participating as a signal molecule for the induction of tolerance to abiotic and biotic stress and stimulating growth, can increase survival. Objective: The objective of this work was to evaluate the effect of salicylic acid on the ex vitro acclimatization of microplants of Laelia autumnalis, Epidendrum sp., and Encyclia sp. Methodology: The experiments started from a permanent source of biological material from microplants of L. autumnalis, Epidendrum sp., and Encyclia sp., grown in Murashige-Skoog (MS) medium. For the treatments, microplants between 0.5 and 0.7 mm were subcultured to MS by adding 0, 1, 10 or 100 μM of AS for 120 ± 4 days under in vitro conditions. At the end of that time, the length of the stem and root, and the fresh weight of the microplants of the 3 species, were evaluated. The plants were subsequently transplanted into seedbeds with pine bark and sphagnum moss and watered twice a week and kept in a growth chamber at room temperature for acclimatization; after 30 days survival was evaluated. Results: Microplants precultured in AS showed differential response in the evaluated variables. Stem and root length and fresh weight increased in Epidendrum sp., and Encyclia sp, especially in the 10 μM treatment, while L. autumnalis showed inhibition in stem and root length and there was only an increase in fresh weight. The microplants of the 3 species precultured with 10 μM of AS significantly increased survival compared to the control. In L. autumnalis and Epidendrum sp., there was also an increase in survival in the preculture of 1 μM of AS and for Encyclia sp. in 100 μM of AS. Implications. Although AS has potential for ex vitro acclimatization of orchids, the variability in response between species should be considered and natural conditions for acclimatization should also be evaluated, with a view to contributing to repopulating orchid communities in their natural environment. Conclusion: AS increases survival under ex vitro conditions, and growth differentially in orchid microplants.